The Surgeon's Responsibility for Plastic Surgery - Lemaini, Mohamed; Atika, Beldjbel (جامعة محمد خيضر بسكرة - كلية الحقوق والعلوم السياسية, 2024)
With the scientific development that society has known, especially in the medical field, medical work has transformed from its general origin of treatment and ridding the patient of disease and pain to operations that seek beauty and beauty. He bears a great responsibility due to the failure to intend treatment, so the legislator, especially the Algerian, must be alerted to the urgent need to develop legislation that adopts the issue of plastic Surgery on the one hand and the responsibility of the person performing it on the other. Your role in this process is crucial, as you are the ones who can enact these necessary laws.
Keywords: المسؤولية القانونية -- العمليات الجراحية -- الجراحة التجميلية -- المهن الطبية